2021
DOI: 10.1186/s40594-021-00314-y
|View full text |Cite|
|
Sign up to set email alerts
|

Authentic STEM research, practices of science, and interest development in an informal science education program

Abstract: Background Two critical challenges in science education are how to engage students in the practices of science and how to develop and sustain interest. The goal of this study was to examine the extent to which high school youth, the majority of whom are members of racial and ethnic groups historically underrepresented in STEM, learn the skills and practices of science and in turn develop interest in conducting scientific research as part of their career pursuits. To accomplish this goal, we app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…And thus, informal STEM experiences may importantly contribute to the development of an individual interest. Some museum programs have designed interventions aimed at developing an individual interest in science by intervening on multiple dimensions simultaneously, such as the program of Habig and Gupta (2021) at American Museum of Natural History (New York, United States). In general, however, museums and other informal learning institutions typically contribute to interest development by offering a context for learning about a topic that is joyful, that asks for cognitive engagement and is driven by curiosity (Hecht et al, 2019), that is by triggering situational interest.…”
Section: Introductionmentioning
confidence: 99%
“…And thus, informal STEM experiences may importantly contribute to the development of an individual interest. Some museum programs have designed interventions aimed at developing an individual interest in science by intervening on multiple dimensions simultaneously, such as the program of Habig and Gupta (2021) at American Museum of Natural History (New York, United States). In general, however, museums and other informal learning institutions typically contribute to interest development by offering a context for learning about a topic that is joyful, that asks for cognitive engagement and is driven by curiosity (Hecht et al, 2019), that is by triggering situational interest.…”
Section: Introductionmentioning
confidence: 99%
“…Recently research has investigated the benefits of informal science learning, and a literature has accumulated showing that participation in STEM youth programs, where adolescents and young people work at informal science learning sites as educators interacting with visitors, plays a key role in the development of science efficacy (Hoffman et al, 2021 ), STEM identity (Hughes et al, 2013 ), positive STEM developmental trajectories (Joy et al, 2023 ) and career preparation (Zhao et al, 2023 ). Adolescents who participated in a science research program at a natural history museum reported that they developed research skills through the program and maintained their science interests outside of the program (Habig & Gupta, 2021 ). This research program also facilitated adolescents’ STEM persistence, such as choosing a STEM career (Habig et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…STEM education is seen as a pioneer of economic growth and innovation, but despite the progress made in the last 20 years, studies have shown that students' interest in STEM fields has decreased and they are moving away from these fields (Habig & Gupta, 2021;Romine & Sadler, 2016;Rozek et al, 2017;Wang, 2013). Similarly, in many reports prepared in Turkey and other countries, students-especially female students-have inadequate tendencies to continue their STEM programs and to pursue their careers in this field (Akgündüz et al, 2015;National Science Foundation [NSF], 2011).…”
Section: Introductionmentioning
confidence: 99%